Paper transistors.
The German firm, Infineon Technologies, has fabricated organic transistors and circuits on commercially available cotton-fiber paper. Infineon worked around the combustion problem by relying on the semiconducting organic material, pentacene, which is workable at relatively low temperatures. The problem of sponginess was addressed by coating the paper with a polymer film less than a micrometer thick. The paper's inherent roughness forced the company to make the transistors about 100 times as large as those you'd find on a silicon circuit, resulting in much slower switching times.
Keywords: Circuit substrate; Cotton-fiber paper; Organic transistors; Paper transistors; Pentacene; Polymer film; Rough fibrous surface; Semiconductor fabrication; Semiconductor substrate; Silicon